?EFFECT OF POLYMERS ON GERMINATION, PLANT HEIGHT AND PERMANENT WILTING POINT OF MAIZE (ZEA MAYS L) AND SOYBEAN (GLYCINE) MAX - CHAUDRY, MUSHTAQ AHMAD; AHMAD, TAHIRA; KHAN, M.F.A (Biological Sciences - PJSIR, 1995)
The study was conducted on sand and clay loam soils in the laboratory to evaluate the influence of soil condition- crs on nor characteristics. Organic manure (Iarm ) art! manure). aquasorb and terrasorb were tested at 0.5 and 1% lv clx. r"lai/c (/l'(I mays L) and xoybca» ((jln'/l1(' mux ; crops were gr()\\Il. The highest germination of maize and SO)· bean \\'as in 1% treated sand. The response ofmaize seed gcnuinaiio» in clay loam was lower compared to that of sand. l.mcrgcncc of maize was more compared \\ ith that Ill' soybean on clay loam. The height of maize plants was greatest in 1°,,, aquasorb-ircarcd clay loam soil \\ hcrcas height of soybean plunts was greatest in 1% tcrrcsorb treat- mcnt. The polvmcr treatment gave a significatnlv greater heigh: ofplants on clay loam than on sand. Longest duration of maize plants survival was in 1% aquasorb-trcaicd clay laom (16.3 days). Soybean seedlings survived for a maxi-mum period of 30 clays and 39 days in 1% aquasorb-trcatcd sane! and 101., aquasorb-trcatcd clay loam soils, rcspcc- tivcly In summary. the polymers had a marked influence on increasing germination. plant height and survival of both maize and soybcun on sand and clay loam soils.